Autophagy-deficient mice develop multiple liver tumors - Takamura, Akito (Cold Spring Harbor Laboratory Press, 2011)
Autophagy is a major pathway for degradation of cytoplasmic proteins and organelles, and has been implicated in tumor suppression. Here, we report that mice with systemic mosaic deletion of Atg5 and liver-specific Atg7(−/−) mice develop benign liver adenomas. These tumor cells originate autophagy-deficient hepatocytes and show mitochondrial swelling, p62 accumulation, and oxidative stress and genomic damage responses. The size of the Atg7(−/−) liver tumors is reduced by simultaneous deletion of p62. These results suggest that autophagy is important for the suppression of spontaneous tumorigenesis through a cell-intrinsic mechanism, particularly in the liver, and that p62 accumulation contributes to tumor progression.